Sports instructors’ job insecurity and turnover intention in South Korea: A moderated mediation model of abusive supervision, work engagement, and perceived organizational support - Kwon-Hyuk Jeong; Heesu Mun; Geon-Ha Jeong (PLoS ONE, 2026)
This study proposes a moderated mediation model examining the impact of job insecurity on turnover intention among non-regular sports instructors in South Korea, through the mediating effect of abusive supervision and the moderated mediation effects of work engagement and perceived organizational support. Analysis of survey data from 267 participants using SPSS and AMOS revealed that job insecurity significantly and positively influenced turnover intention and abusive supervision, with abusive supervision demonstrating a partial mediating effect on the relationship. Furthermore, both work engagement and perceived organizational support exhibited significant moderated mediation effects, such that the mediated pathway strengthened when these factors were low. These findings underscore the necessity of leadership training, psychological support enhancement, and stable employment policies to mitigate employment instability in the sports industry, contributing to human resource management theory in sports management based on JD-R theory and conservation of resources theory.